Simbol Dalam Penerapan Teori Keindahan Oleh Johann Joachim Winckelmann - Nurmaizan, Hamri (Universiti Malaysia Sarawak (UNIMAS), 2016)
This research is the study of the symbols based on the theory of beauty by Johann Joachim Winckelmann. Researcher will study the theory of beauty by Johann Joachim Winckelmann that will be applied to the artwork. To obtain information, the researcher will use several methods such as primary, secondary and observation. In addition, researcher will apply the beauty of concept or theory that has been obtained in the making of an artwork. The artwork that use symbol as a subject matter with the application of the theory by Johann Joachim Winckelmann.